Not Just Privilege: The Moderating Role of Financial Knowledge in The Relationship Between Parental Income and Locus of Control on Youth Financial Management - Baiq Reinelda Tri Yunarni; Elok Sri Utami; Dedy Iswanto; Fuzail Muhammad (Jurnal Ilmiah Manajemen & Bisnis, 2026)
This study examined personal financial management behavior of Generation Z within the digital economic landscape, specifically analyzing how it is driven by their internal Locus of Control and the level of parental income and the moderating role of Financial Knowledge. Using a quantitative approach with Structural Equation Modeling (SEM) through SmartPLS, data were gathered through an online survey of 231 Generation Z respondents in Mataram City. The results showed a significant positive impact on financial management behavior from both parental income and locus of control, these indicated that both psychological self-regulation and family economic background play important roles in shaping responsible financial habits, while Financial Knowledge did not significantly moderate these relationships. Additionally, Locus of Control was found to mediate the relationship between Parental Income and Financial Management Behavior, highlighting the importance of internal motivation in financial decision-making. Overall, the findings suggest that improving financial management among Generation Z requires not only strengthening financial literacy but also fostering personal responsibility and supportive socio-economic environments, providing useful implications for educators, policymakers, and families in developing more comprehensive financial education strategies in the digital era.